Archives, museums and sacred storage: dealing with the afterlife of the Truth and Reconciliation Commission of Canada - Milton, Cynthia E. (International journal of transitional justice, 2019)
The Canadian Truth and Reconciliation Commission (TRC) acquired over 1,200 material submissions through the gifts it received at its events. Though other TRCs mention objects in their records, the gift-giving practice that became central to TRC events in Canada was unprecedented, and so is its large collection of TRC-gifted objects today. The Canadian TRC is thus unique and faces the challenges of categorizing, preserving, displaying and honouring these material artefacts. What has been the post-TRC life of these objects and art pieces? What is their role in creating a collective memory of residential schools and how might they promote reconciliation? This article shows that the post-TRC life of the objects opens up new museological spaces and practices through the ways the objects are curated (or not) for remembering and learning about residential schools according to Indigenous protocols and ways of thinking and feeling.